2019
DOI: 10.31223/osf.io/3jkcp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global survey on the perceptions and impacts of gender inequality in the Earth and space sciences

Abstract: The leaky pipeline phenomenon refers to the disproportionate drop-out of female scientists at higher academic career levels and is a major problem in the natural sciences. Identifying the underlying causes is challenging, and thus solving the problem remains difficult. To better understand the reasons for the leaky pipeline, we assess the perceptions and impacts of gender bias and imbalance—two major drivers of the leakage—at different academic career levels with an anonymous survey in geoscience academia (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…ecent research points to a persistent disparity in the representation and inclusion of individuals in the geosciences based on gender, ability status, ethnicity and race, and sexual orientation [1][2][3][4][5][6][7][8][9][10][11][12][13] . Mentoring and role modeling are recognized as part of a solution for achieving greater recruitment and retention of students from the underrepresented groups in science, technology, engineering, and mathematics (STEM) fields, such as the geosciences 3,[14][15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…ecent research points to a persistent disparity in the representation and inclusion of individuals in the geosciences based on gender, ability status, ethnicity and race, and sexual orientation [1][2][3][4][5][6][7][8][9][10][11][12][13] . Mentoring and role modeling are recognized as part of a solution for achieving greater recruitment and retention of students from the underrepresented groups in science, technology, engineering, and mathematics (STEM) fields, such as the geosciences 3,[14][15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…Second, because women employed at such positions can always be taught that they only got it because of their gender, not their capacities" ID12. A global survey targeting Earth and Space scientists by Popp et al (2019) clearly showed the divided opinion on quotas. They noted how quotas' favour tends to be gendered, with 44.9% of women and 27.9% of men sharing a favourable opinion and career stage related.…”
Section: Professional Development and Gender Equitymentioning
confidence: 99%
“…Could it be that a fixation on data density is not compatible with the questions relevant to the communities most impacted by landscape change in the Anthropocene, or to the methods most suitable or accessible for conducting research that is relevant there? Optimistically, we hope that asking a greater breadth of questions might also help improve on the diversity crisis that plagues the earth sciences (Bernard & Cooperdock, 2018; King et al, 2018; Popp et al, 2019).…”
Section: Looking Forward—a Holistic Science Needed In the Anthropocenementioning
confidence: 99%